PENGARUH PARTISIPASI ANGGARAN, MOTIVASI KERJA, KEADILAN PROSEDURAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL APARAT SATUAN PERANGKAT DAERAH (Studi Empiris Pada SKPD Kabupaten Brebes) - Rizki Armanda, 11.05.52.0125; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2017)
This study aims to examine the budgetary participation, motivation, procedural justice, organizational commitment to managerial performance SKPD apparatus. The population in this study is the structural officials Brebes District Government, consisting of Echelon II, III, and IV are still active duty. The sampling technique used purposive sampling based on various criteria: have a minimum term of two years. Test equipment using multiple linear regression.Â The results of this study indicate that: Participation budgetary positive and significant impact on managerial performance SKPD apparatus. Job motivation and significant positive effect on managerial performance SKPD Justice officials procedural positive and significant impact on managerial performance SKPD apparatus. Organizational commitment and significant positive effect on managerial performance SKPD apparatus.Keywords:Â Budget Participation, Motivation, Procedural Justice, Organizational Commitment and Managerial Apparatus Performance SKPD